The Fra-1: Novel role in regulating extensive immune cell states and affecting inflammatory diseases - He, Yu-Yao; Zhou, Hai-Feng; Chen, Lu; Wang, Yan-Ting; Xie, Wan-Li; Xu, Zhen-Zhen; Xiong, Yue; Feng, Yi-Qi; Liu, Guo-Yang; Li, Xia; Liu, Jie; Wu, Qing-Ping (Frontiers in Immunology, 2022)
Fra-1, a member of transcription factor activator protein (AP-1), plays an important role in cell proliferation, apoptosis, differentiation, inflammation, oncogenesis and tumor metastasis. Aberrant high expression of Fra-1 has been found in various tumors, including breast cancer, lung cancer, and stomach cancer, etc., and correlated with poor prognosis. Accumulating evidence suggest that the malignancy and invasive ability of tumors can be significantly impaired by directly targeting Fra-1. Besides, the effects of Fra-1 are gradually revealed in immune and inflammatory settings, such as arthritis, pneumonia, psoriasis and cardiovascular disease. These regulatory mechanisms that orchestrate immune and non-immune cells underlie Fra-1 as a potential therapeutic target for a variety of human diseases. In this review, we focus on the current knowledge of Fra-1 in immune system, highlighting its unique importance in regulating tissue homeostasis. In addition, we also discuss the possible critical intervention strategy in diseases, which also outline future research and development avenues.